Overview of Control Programs for Twenty-Four Infectious Cattle Diseases in Italy - Tamba, Marco; Pallante, Ivana; Petrini, Stefano; Feliziani, Francesco; Iscaro, Carmen; Arrigoni, Norma; Di Sabatino, Daria; Barberio, Antonio; Cibin, Veronica; Santi, Annalisa; Ianniello, Marco; Ruocco, Luigi; et al. (Frontiers in Veterinary Science, 2021)
The cattle industry is a major driving force for the Italian agricultural sector totalling about 5.6 million heads for dairy and meat production together. It is particularly developed in the northern part of the country, where it covers 70% of the whole Italian cattle population. The cattle industry development in the rest of the country is hampered by the hard orography of the territories and a variety of socioeconomic features leading to the persistence of the traditional rural farming systems. The differences in the farming systems (industrial vs traditional) also affect the health status of the farms. Whereas Enzootic Bovine Leukosis (EBL) is almost eradicated across the whole country, in Southern Italy where Bovine Tuberculosis and Brucellosis are still present and Bluetongue is endemic due to the presence of the competent vector (Culicoides imicola), less investments are aimed at controlling diseases with economic impact or at improving farm biosecurity. On the other hand, with the eradication of these diseases in most part of the country, the need for reducing the economic burden of non-regulated endemic disease has emerged and control programs (CPs) for specific diseases have been implemented at regional level, based on the needs of each territory (for instance common grazing or trading with neighbouring countries). This explains the coexistence of different types of programs in force throughout the country. Nowadays in Italy, among cattle diseases with little or no EU regulations only three are regulated by a national CP: Enzootic Bovine Leukosis, Bluetongue and Paratuberculosis, while Bovine Genital Campylobacteriosis and Trichomonosis are nationwide controlled only in breeding bulls. For some of the remaining diseases (Infectious Bovine Rhinotracheitis, Bovine Viral Diarrhoea, Streptococcus agalactiae) specific CPs have been implemented by the regional Authorities, but for most of them a CP does not exist at all. However, there is a growing awareness among farmers and public health authorities that animal diseases have a major impact not only on the farm profitability but also on animal welfare and use of antibiotics in livestock. It is probable that in the near future other CPs are going to be implemented.